2020
DOI: 10.1094/pdis-11-19-2431-re
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping a Broad-Spectrum Powdery Mildew Resistance Gene in Chinese Landrace Datoumai,PmDTM, and Its Relationship withPm24

Abstract: Powdery mildew, caused by the biotrophic fungal pathogen Blumeria graminis f. sp. tritici (Bgt), is a globally important wheat disease causing severe yield losses, and deployment of resistant varieties is the preferred choice for managing this disease. Chinese wheat landrace Datoumai was resistant to 22 of 23 Bgt isolates at the seedling stage. Genetic analysis based on the inoculation of Bgt isolate E09 on the F1, F2, and F2:3 populations derived from the cross Datoumai × Huixianhong revealed that the powdery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…China has abundant wheat landraces, and the desirable traits can be readily transferred from landraces to some elite common wheat cultivars. So far, five genes that confer powdery mildew resistance have been identified in Chinese wheat landraces, including Pm63 (PI628024) [31], Pm61 (Xuxusanyuehuang) [15], Pm59 (PI181356) [27], Pm47 (Hongyanglazi) [26], Pm24 (Chiyacao/Baihulu) [32,33], Pm11 (Chinese spring) [34], Pm5e (Fuzhuang 30) [35,36], and Pm2c (Laomai) [37], which were mapped on chromosomal arms of 2BL, 4AL, 7Al, 7BS, 1DS, 6BS, 7BL, and 5DS, respectively. It has been reported that chromosome 1B contains three powdery mildew resistance genes, namely Pm28, Pm32, and Pm39, and their specific locations are chromosomal arms of 1B, T1BL.1SS, and 1BL, respectively [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…China has abundant wheat landraces, and the desirable traits can be readily transferred from landraces to some elite common wheat cultivars. So far, five genes that confer powdery mildew resistance have been identified in Chinese wheat landraces, including Pm63 (PI628024) [31], Pm61 (Xuxusanyuehuang) [15], Pm59 (PI181356) [27], Pm47 (Hongyanglazi) [26], Pm24 (Chiyacao/Baihulu) [32,33], Pm11 (Chinese spring) [34], Pm5e (Fuzhuang 30) [35,36], and Pm2c (Laomai) [37], which were mapped on chromosomal arms of 2BL, 4AL, 7Al, 7BS, 1DS, 6BS, 7BL, and 5DS, respectively. It has been reported that chromosome 1B contains three powdery mildew resistance genes, namely Pm28, Pm32, and Pm39, and their specific locations are chromosomal arms of 1B, T1BL.1SS, and 1BL, respectively [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Pm21 is not suggested for use alone in wheat breeding programs although it has low frequency occurrence in some regions. It would be great if it could be pyramided with other effective Pm resistance genes such as Pm12, Pm24 [58], and Pm68 [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the PmDTM gene encoding receptor-like serine/threonine-protein kinase in wheat can improve the resistance of wheat to Blumeria graminis f. sp. tritici [30]. Similarly, CsWAKL08 gene encoding a wall-associated receptor-like kinase was found to regulate resistance against Xanthomonas citri subsp.…”
Section: Comparative Transcriptome Analysismentioning
confidence: 99%